Selective Detection of Toxic Gases by Arrays of Single-Layer Graphene Sensors Functionalized with Nanolayers of Different Oxides - Margus Kodu; Martin Lind; Valter Kiisk; Indrek Renge; Raivo Jaaniso (Proceedings)
Graphene provides an ideal platform for chemiresistive gas sensors as the material is fully exposed to the surrounding environment. For practical use in an ambient atmosphere, its sensitivity and selectivity should be evoked by functionalization by defects and dopants or by decoration with nanophases of metals or metal oxides. Here, we demonstrate a few successful cases of selectivity enhancement by functionalizing the graphene with different oxide layers and applying machine learning to the resulting sensor array.